2005
DOI: 10.1016/j.finel.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive computations on conforming quadtree meshes

Abstract: In this paper, the quadtree data structure and conforming polygonal interpolants are used to develop an h-adaptive 7 finite element method. Quadtree is a hierarchical data structure that is computationally attractive for adaptive numerical simulations. Mesh generation and adaptive refinement of quadtree meshes is straight-forward. However, 9 finite elements are non-conforming on quadtree meshes due to level-mismatches between adjacent elements, which results in the presence of so-called hanging nodes. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 34 publications
(25 reference statements)
2
83
0
Order By: Relevance
“…One of the simplest is using quad tree structures (in 2D) and has been used in the context of finite volume method in [14][15][16], for FEM in [17], and with the meshfree element-free Galerkin method [18], where level-1 quad-tree structures are employed even though this is not explicitly mentioned in the paper. The level-1 (or 1-irregular) grid refinement has been originally introduced in [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the simplest is using quad tree structures (in 2D) and has been used in the context of finite volume method in [14][15][16], for FEM in [17], and with the meshfree element-free Galerkin method [18], where level-1 quad-tree structures are employed even though this is not explicitly mentioned in the paper. The level-1 (or 1-irregular) grid refinement has been originally introduced in [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This problem is solved in Reference [9] using the exact solution to estimate the error. In this paper, the problem is solved using the residual-based error estimator.…”
Section: Examplementioning
confidence: 99%
“…Special techniques have been used to construct conforming approximations over quadtree meshes: constraining hanging nodes to corner nodes [1], adding temporary elements to construct a compatible mesh [2,3], Lagrange multipliers and penalty or Nitsche's method to impose constraints [4,5], using hierarchical enrichment [6,7] or B-splines [8], and natural neighbor basis functions [9,10]. In this paper the method developed in Reference [9] is employed to resolve the problem associated with the presence of hanging nodes. This technique is based on the polygonal finite element method introduced in References [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Tabarraei and Sukumar [11] demonstrated that, for the special case of quadtree meshes, for the Poisson equation and for the elasticity problem, the stiffness matrix of a subelement is the same as the stiffness matrix of the parent. Suzuki and Tabata [20] also showed the importance of reusing previous calculations studying the structure of the finite element mass and stiffness matrices of congruent subdomains (each of them being an image of a reference subdomain by an affine transformation, see [20] for further details).…”
Section: Hierarchical Properties Between Geometrically Similar Elementsmentioning
confidence: 99%
“…The use of a structured element splitting, as in the quadtree and octree methods [8,11] is rather efficient as it allows improving the storage of the mesh related information. However, other splitting techniques, that could be termed non-structured element splitting techniques, are more flexible as they can be applied on any mesh.…”
Section: Introductionmentioning
confidence: 99%